Evaluating iron and zinc bioavailability in biofortified potatoes to reduce malnutrition in the Andes. Project profile. - International Potato Center (International Potato Center, 2019)
Iron and zinc deficiency are widespread problems in developing countries. Scientists at CIP have bred iron- and zinc-biofortified potatoes to contribute to efforts to reduce malnutrition in the Andes and other regions where potato is a staple crop. Bioavailability studies will determine how much iron and zinc the body absorbs from those potatoes and their potential for reducing anemia and zinc deficiency.